The supercritical processing of mammalian cells for applications in tissue engineering - Ginty, Patric J. (2006)
Conventional methods of combining mammalian cells and synthetic polymers for tissue engineering applications are frequently problematic. This is due to the incompatibility between the sensitive cell component and the harsh polymer processing environments required to form the desired porous scaffold e. g. high temperatures and organic solvents. This results in the necessity for an often inefficient and time consuming two step scaffold seeding process, whereby mammalian cells are added to a pre-fabricated polymer scaffold. High pressure or supercritical CO2 (scCO2) processing is a method of fabricating porous polymer scaffolds at ambient temperatures and without using organic solvents. When pressurised, CO2 becomes highly soluble in a variety of amorphous polymers such as poly(DL-lactic acid) (PDLLA) to produce a high viscosity liquid. Subsequent decompression causes the formation of gas bubbles that become permanent as the polymer vitrifies. Based upon technology at the University of Nottingham, we hypothesised that mammalian cells could be incorporated into poly(DL-lactic acid) (PDLLA) scaffolds using a single step scCO2 process. This would not only make the process more rapid, but it would remove the inefficient scaffold seeding step required in most cell based tissue engineering strategies. Mammalian cells were subject to a range of high pressure CO2 and N2 processing conditions and assessed for cell survival. It was discovered that primary hepatocytes, meniscal fibrochondrocytes, myoblastic C2C12s and 3T3 fibroblasts could survive after exposure to both high pressure gases on a time and pressure dependent basis. Cells exposed to scCO2 for one minute were then assessed for both gene and enzyme function.Using a microarray, it was found that only eight genes (out of 9000) in murine C2C12 cells were significantly down-regulated when compared to untreated cells. Continued cell function was confirmed by measuring BMP-2 induced alkaline phosphatase activity as a measure of osteogenic differentiation in myoblastic C2C12 cells. Alkaline phosphatise activity was indistinguishable between untreated cells and cells exposed to scCO2 for one minute. Additional enzyme and receptor function was confirmed by measuring cytochrome P450 activity in primary hepatocytes after one minute of scCO2 processing. In the second half of the study, these short processing times were found to be sufficient to plasticise and foam porous PDLLA scaffolds. Therefore, cells were incorporated into the biodegradable PDLLA foams by pre-mixing the cell suspension with the polymer powder and exposing to scCO2. Subsequent decompression caused the polymer to foam with the cells trapped within the porous structure. Despite the presence of the plasticised PDLLA, cell survival was confirmed by both an Alamar B1ueTM assay and LIVE/DEADTM staining. Osteogenic differentiation on the scaffolds was confirmed by a stain and assay for BMP-2 induced alkaline phosphatase activity. Finally, a second generation processing piece of processing apparatus was designed that permitted mammalian cells to be passed into a pressurised vessel containing preplasticised PDLLA using a novel high-pressure CO2 injection system. This was made possible by constant optimisation of the high pressure apparatus and the introduction of a cell delivery valve. When injected at high pressures cell survival was found to be reduced when compared with previous experiments although this was likely to be due to the additional mechanical trauma caused by the injection process. Despite this, the live cell population was shown to retain its osteogenic differentiation capacity when induced with BMP-2. With further optimisation of the delivery method, cells may survive this process in sufficient numbers to suggest that it could be used as a method of seeding tissue engineering scaffolds in the future. This development could remove the limitations place on polymer processing time by the finite survival period of the cells, permitting tuning of the scaffold structure to suit the application. In summary, this study has demonstrated that mammalian cells can be incorporated into biodegradable PDLLA scaffolds using a rapid, one-step scCO2 process without the use of toxic solvents or elevated temperatures. Furthermore, the development of the high pressure injection system could allow cells to be incorporated during the fabrication step, removing the restrictions on polymer processing. This technique could be used for the rapid production of tissue cell loaded engineering scaffolds and other associated biotechnological applications where cells and synthetic polymers are combined, such as cell therapy and recombinant protein production.